Demanding the Cherokee Nation : Indian autonomy and American culture, 1830-1900 - Denson, Andrew (Indians of the Southeast., 2004)
Demanding the Cherokee Nation examines nineteenth-century Cherokee political rhetoric to address an enigma in American Indian history: the contradiction between the sovereignty of Indian nations and the political weakness of Indian communities. Making use of a rich collection of petitions, appeals, newspaper editorials, and other public records, Andrew Denson describes the ways in which Cherokees represented their people and their nation to non-Indians after their forced removal to Indian Territory in the 1830s. He argues that Cherokee writings on nationhood document a decades-long effort by tribal leaders to find a new model for American Indian relations in which Indian nations could coexist with a modernizing United States.